Jutland, 1916 Death in the grey wastes - Steel, Nigel 1962- (Cassell Military, 2003)
Based on letters, diaries, unpublished memoirs, interviews, books and other sources, this detailed study examines the whole event from the perspective of participants on both sides and from all ranks. Relive the dramatic intensity of the battle, and the all too sad aftermath.